Deletion of human metapneumovirus M2-2 increases mutation frequency and attenuates growth in hamsters - Schickli, Jeanne H; Kaur, Jasmine; MacPhail, Mia; Guzzetta, Jeanne M; Spaete, Richard R; Tang, Roderick S (Virology journal, 2008)
Human metapneumovirus (hMPV) infection can cause acute lower respiratory tract illness in infants, the immunocompromised, and the elderly. Currently there are no licensed preventative measures for hMPV infections. Using a variant of hMPV/NL/1/00 that does not require trypsin supplementation for growth in tissue culture, we deleted the M2-2 gene and evaluated the replication of rhMPV/DeltaM2-2 virus in vitro and in vivo. In vitro studies showed that the ablation of M2-2 increased the propensity for insertion of U nucleotides in poly-U tracts of the genomic RNA. In addition, viral transcription was up-regulated although the level of genomic RNA remained comparable to rhMPV. Thus, deletion of M2-2 alters the ratio between hMPV genome copies and transcripts. In vivo, rhMPV/DeltaM2-2 was attenuated compared to rhMPV in the lungs and nasal turbinates of hamsters. Hamsters immunized with one dose of rhMPV/DeltaM2-2 were protected from challenge with 106 PFU of wild type (wt) hMPV/NL/1/00. Our results suggest that hMPV M2-2 alters regulation of transcription and influences the fidelity of the polymerase complex during viral genome replication. In the hamster model, rhMPVDeltaM2-2 is attenuated and protective suggesting that deletion of M2-2 may result in a potential live vaccine candidate. A more thorough knowledge of the hMPV polymerase complex and the role of M2-2 during hMPV replication are being studied as we develop a potential live hMPV vaccine candidate that lacks M2-2 expression.